Medieval English and Dutch Literatures the European context : Essays in Honour of David F. Johnson. - Tracy, Larissa (Boydell & Brewer, Limited, 2022)
This collection honours the scholarship of Professor David F. Johnson, exploring the wider view of medieval England and its cultural contracts with the Low Countries, and highlighting common texts, motifs, and themes across the textual traditions of Old English and later medieval romances in both English and Middle Dutch.